New Forms of Anti-Hindutva Resistance: Critical Feminist Struggle and Diaspora Activism against Hindutva in India and Abroad - Khalid, Iram (Annals of Human and Social Sciences, 2024)
India, a country that takes pride in its diversity has witnessed a growing trend of otherization of minorities since the ascension of Hindutva: a nationalist ideology that advocates Hindu hegemony, to the policy circles. There has been a sufficient scholarly endeavor to explain the emergence and transnational proliferation of Hindutva, and the ways it has transformed India’s sociopolitical landscape. However, there is a little scholarship on the resistance against this exclusionist design, and even less on the feminist and particularly Muslim women led activism. The research delves into the emergent modalities of anti-Hindutva resistance through the dual praxes of critical feminist struggle and intersectionality by drawing exclusive focus on the resistance led by Muslim women. By employing an interdisciplinary approach that combines both qualitative and case-study based analysis of activist’s practices, mobilization strategies and online engagement mechanisms, this research elucidates how feminist movements and organizations create counter narratives to Hindutva’s exclusionary project. The findings reveal that feminist protests serve to subvert the patriarchal structures and create space for an inclusive form of citizenship. The research illustrates that Muslim women’s activism is beyond the conventional practices of a protest movement, employing multifold strategies to contest Islamophobia, communal violence and patriarchal barriers. The research contributes to the global discourse on democratic values and social justice, thus illuminating the way forward for policymakers and activists against majoritarianism around the world.